LOS BRACONIDOS (HYMENOPTERA: BRACONIDAE) COMO GRUPO PARAMETRO DE BIODIVERSIDAD EN LAS SELVAS DECIDUAS DEL TROPICO: UNA DISCUSION ACERCA DE SU POSIBLE USO - Delfín González, Hugo; Burgos Ruíz, David (Instituto de Ecología, A.C., 2000)
The aim of this essay is to propose the use of a parasitoid wasp family (Hymenoptera: Braconidae) as a parameter group for describing the biodiversity in tropical deciduous forest in order to evalúate and monitor the effect of anthropogenic activities in this ecosystems. The importance of this group is related to their regulating role on host populations, being an important alternativa for biological pest control by natural enemies instead of the application of pesticidas. Eight criteria are considerad to define them as a parameter group. In conclusión, the braconids, especially the koinobiont species can be used as parameter groups to determine the human impact on the natural communities and to estímate the species richness in a given región. In addition, this study provides Information related to the diversity of this group through a latitudinal gradient.